Proximal Fibular Osteotomy in the Management of Osteoarthritis of Medial Compartment of Knee Joint - Ahmed, Masroor (Cureus, 2020)
Introduction: This study was conducted to evaluate the efficacy of proximal fibular osteotomy (PFO) in terms of pain relief, and improvement in function in medial compartment osteoarthritis (OA) of the knee joint. Materials and methods: This case series study was conducted at the Shaheed Mohtarma Benazir Bhutto Medical College Lyari and United Medical and Dental College of Karachi. Patients with medial compartment knee joint OA were included in the study and patients with bicompartmental or tricompartmental OA, inflammatory joint disease, valgus knee deformity, morbid obesity, or any infectious pathology involving the knee joint were excluded from the study. The medial and lateral joint spaces were measured and recorded preoperatively and postoperatively. Pre- and postoperative values of visual analog scale (VAS) results and the Oxford knee score were recorded. A PFO was performed after getting informed written consent. Results: A total of 60 patients were enrolled in the study; 16 (26.7%) were men, and 44 (73.3%) were women. The mean age of patients was 51.8 ± 4.1 years. The mean preoperative medial joint space measurement on standard anteroposterior radiograph was 1.45 ± 0.28 mm. The mean preoperative lateral joint space was 8.86 ± 1.27 mm. The recorded mean preoperative Oxford knee score was 20.82 ± 1.97 mm. Recorded levels of mean postoperative medial joint space improved to 4.63 ± 0.668 mm, and mean postoperative lateral joint space was 4.72 ± 0.79 mm. Mean recorded levels of VAS for pain postoperatively were 2.32 ± 0.792, which improved significantly from 7.90 ± 0.79. Conclusions: PFO is a good surgical technique for pain relief and functional improvement in patients suffering from medial compartment OA.